Functional genetic elements for controlling gene expression in Cupriavidus necator H16 - Alagesan, Swathi; Hanko, Erik K.R.; Malys, Naglis; Ehsaan, Muhammad; Winzer, Klaus; Minton, Nigel P. (American Society for Microbiology., 2018)
A robust and predictable control of gene expression plays an important role in synthetic biology and biotechnology applications. Development and quantitative evaluation of functional genetic elements such as constitutive and inducible promoters, as well as ribosome binding sites (RBSs), are required. In this study, we design, build and test promoters and RBSs for controlling gene expression in the model lithoautotroph Cupriavidus necator H16. A series of variable-strength, insulated, constitutive promoters exhibiting predictable activity within more than 700-fold dynamic range is compared to the native PphaC, with the majority of promoters displaying up to a 9-fold higher activity. Positively (AraC/ParaBAD-L-arabinose and RhaRS/PrhaBAD-L-rhamnose) and negatively (AcuR/PacuRI-acrylate and CymR/Pcmt-cumate) regulated inducible systems are evaluated. By supplying different concentrations of inducers, over a 1000-fold range of gene expression levels is achieved. Application of inducible systems for controlling expression of isoprene synthase gene ispS leads to isoprene yields that exhibit a significant correlation to the reporter protein synthesis levels. The impact of designed RBSs and other genetic elements such as mRNA stem-loop structure and A/U- rich sequence on the gene expression is also evaluated. A second-order polynomial relationship is observed between the RBS activities and isoprene yields. This study presents quantitative data on regulatory genetic elements and expands the genetic toolbox of C. necator.